THE IMPACT OF THE DEVELOPMENT OF WATER RESOURCES ON ENVIRONMENT IN ARID INLAND RIVER BASINS OF HEXI REGION, NORTHWESTERN CHINA - Ji X.; Kang E.; Chen R.; Zhao W.; Zhang Zh.; Jin B. (My University, 2006)
Water resources use is a key parameter in the hydrological cycle, especially in arid inland of Northwest China, groundwater movement and circulation processes are closely related to the surface water, while recoverable and renewable groundwater mainly comes from the conversion of surface river water, and there is extensive transfer among rainfall, surface water and groundwater. Human activity, in particular, large-scale water resources exploitation and development associated with dramatic population growth in the last decades, has led to tremendous changes in the water regime. There are misuse and wastage of surface water with traditional multi-channel irrigation for most rivers, which in turn leads to over-exploitation of groundwater to augment supplies. This situation has been exacerbated by rapid population growth and socio-economic development, with decreased irrigational systems return to groundwater due to the irrigation system in the middle reaches of rivers in the Hexi region becoming better. The investigations of this study revealed that over the last decades, man-made oases have developed rapidly in various inland river basins. With the increasing human demand for water, the contradiction between water demand and water supply is becoming increasingly acute and the amount of groundwater usage significantly increased. Notwithstanding the annual surface water from mountains is relatively stable in the Hexi region, the recharges of groundwater have been reduced by 11.1%, with a maximum reduction of 50% in the Shiyang River basin. Groundwater abstraction increased by approximately six times, particularly in the Shiyang River basin, groundwater abstraction exceeds recharge by 4.1×108 m3 year−1 in recent decades. Consequently, the groundwater level has declined widely by 3–16 m, with a maximum decline of 45 m in several groundwater observation wells in the Minqin basin on the lower reaches of the Shiyang River basin. These cause serious human activity-induced environmental problems, such as water-quality deterioration, vegetation degradation, soil salinization and land desert desertification, etc. It is suggested that modernized irrigation technology and new regulation to cover water resources management and allocation with the river basins are urgently needed to achieve a sustainable development. The aim of this study is to analyze the impact of the development of water resources on the environment in arid inland river basins in Northwestern China, which were analyzed by comparing the three main river basins (i.e., the Shuilei, the Heihe and the Shiyang River basins) with different water resources development cases.
Keywords: WATER RESOURCES DEVELOPMENT; ENVIRONMENT; HUMAN ACTIVITY; ARID INLAND RIVER BASIN; CHINA